Penggunaan Alat Peraga Kereta Satuan Volume untuk Meningkatkan Hasil Belajar Matematika - Rahayu, Bangun Sri (Jurnal Didaktika Pendidikan Dasar, 2021)
This paper in the form of classroom action research aims to improve the mathematics learning achievement of grade 6 students at SD Negeri 02 Penakir by using the train props for volume units. The learning improvement setting is for grade 6 students in the 1st semester of Mathematics at SD Negeri 02 Penakir, Pemalang Regency where the researcher teaches. This classroom action research consists of 2 cycles in one basic competency. During the learning process, observations were made on the performance of the teacher as a researcher, and an assessment was made of students through test sheets. Other findings during the learning process were discussed between the researcher and the observer, equipped with data from observations made by reflection at each meeting. The results of the research in the first cycle and the second cycle showed an increase in student learning achievement. The results of the assessment of student learning achievement are the First cycle: 70.8 with 68% learning completeness, in the second cycle: 82 with 88% learning completeness. Based on the results of the study, it can be concluded that the learning process using the volume unit train props in mathematics can improve the learning outcomes of students in Class 6 SD Negeri 02 Penakir, Pemalang Regency.